Предмет: Математика,
автор: quin1
как решить такое уравнении (x-28)+53=60 55-(42-x)=35 (25+x)-32=15 падробно
Ответы
Автор ответа:
1
(x-28)+53=60
(x-28)=60-53
x-28=7
x=7+28
x=35
55-(42-x)=35
-(42-x)=35-55
x-42=-20
x=-20+42
x=22
(25+x)-32=15
25+x=15+32
25+x=47
x=47-25
x=22
(x-28)=60-53
x-28=7
x=7+28
x=35
55-(42-x)=35
-(42-x)=35-55
x-42=-20
x=-20+42
x=22
(25+x)-32=15
25+x=15+32
25+x=47
x=47-25
x=22
Аноним:
quin тебе все понятно?
Автор ответа:
4
(Х-28)+53=60
Х-28=60-53
Х-28=7
Х=28+7
Х=35
Ответ : 35
55-(42-x)=35
42-х=55-35
42-х=20
Х=42-20
Х=22
Ответ:22
(25+x)-32=15
25+х=15+32
25+х=47
Х=47-25
Х=22
Ответ:22
Похожие вопросы
Предмет: История,
автор: Dicorn
Предмет: Немецкий язык,
автор: shitik2103
Предмет: Английский язык,
автор: cat123459
Предмет: Алгебра,
автор: Kadochnikova11
Предмет: Алгебра,
автор: Аноним